Parasite Inspection in Five Commercially Important Oyster Species (Mollusca: Bivalvia) of Pakistan - Nuzhat Afsar; Ghazala Siddiqui; David Roberts (Journal of Basic & Applied Sciences, 2014)
A total of five native oyster species namely; Crassostrea gryphoides, C. madrasensis, C. glomerata, Ostrea nomades and Saccostrea cucullata were collected from three sites: Buleji of Sindh coast; Hub and Jiwani of Balochistan coast, Pakistan. Parasitic inclusion was present only in histological sections of O. nomades and S. cucullata at Buleji.Individuals of O. nomades found to be infected with protozoan parasite Nematopsis speciesand Proctoeces sp. trematodeparasite. Additionally, unknown parasitic cyst was observed at outer epithelium in a male gonadal section of S. cucullata. There is no previous record in literature of pathogens in oyster species at Buleji.